Intraspecific diversity and genetic structure in the widespread macroalga Agarophyton vermiculophyllum. Issue 5 (22nd July 2021) - Krueger‐Hadfield, Stacy A.; Byers, James E.; Bonthond, Guido; Terada, Ryuta; Weinberger, Florian; Sotka, Erik E.
Abstract : Single‐gene markers, such as the mitochondrial cox 1, microsatellites, and single‐nucleotide polymorphisms are powerful methods to describe diversity within and among taxonomic groups and characterize phylogeographic patterns. Large repositories of publicly‐available, molecular data can be combined to generate and evaluate evolutionary hypotheses for many species, including algae. In the case of biological invasions, the combination of different molecular markers has enabled the description of the geographic distribution of invasive lineages. Here, we review the phylogeography of the widespread invasive red macroalga Agarophyton vermiculophyllum (synonym Gracilaria vermiculophylla ). The cox 1 barcoding provided the first description of the invasion history and hinted at a strong genetic bottleneck during the invasion. Yet, more recent microsatellite and SNP genotyping has not found evidence for bottlenecks and instead suggested that genetically diverse inocula arose from a highly diverse source population, multiple invasions, or some mix of these processes. The bottleneck evident from cox1 barcoding likely reflects the dominance of one mitochondrial lineage, and one haplotype in particular, in the northern source populations in Japan. Recent cox 1 sequencing of A. vermiculophyllum has illuminated the complexity of phylogeographic structure in its native range of the northwest Pacific Ocean. For example, the western coast of Honshu in the Sea of Japan displays spatial patterns of haplotypic diversity with multiple lineages found together at the same geographic site. By consolidating the genetic data of this species, we clarify the phylogenetic relationships of a well‐studied macroalga introduced to virtually every temperate estuary of the Northern Hemisphere.